Dosing Evaluation of Continuous Intravenous Fentanyl Infusions in Overweight Children: A Pilot Study - Gish, Emily C (Pediatric Pharmacy Advocacy Group, 2011)
OBJECTIVES: The purpose of this study was to assess the appropriateness of weight-based dosing of continuous intravenous infusion of fentanyl in overweight/obese versus normal-weight children admitted to the pediatric intensive care unit (PICU). METHODS: This retrospective, pilot study included 5- to 12-year-old children admitted to the PICU over a 2-year period who received continuous intravenous infusion fentanyl for ≥ 4 days. The overweight/obese group included children with a body mass index (BMI) ≥ 85th percentile, while the control group included children with BMI < 85th percentile. The primary objective was to compare the number of fentanyl continuous intravenous infusion dosage changes required per day to achieve adequate sedation between groups. Secondarily, opioid withdrawal symptoms following the discontinuation of fentanyl and concomitant sedative/analgesic regimens were analyzed between groups. Student t tests and chi-square analyses were performed as appropriate, with an a priori alpha of p≤0.05. RESULTS: Sixteen normal-weight and 15 overweight/obese patients with 18 and 16 individual infusions were identified, respectively. No statistical difference was found between groups for the number of dosage changes per day, 0.92 versus 0.69 (p=0.16). Five patients in each group experienced withdrawal (p=0.71). The total number of concomitant bolus doses received was greater in the overweight/obese group but did not reach statistical significance. CONCLUSIONS: There was a numerical, but statistically nonsignificant difference in the number of sedative/analgesic bolus doses and dosing changes per day between groups. Larger studies are warranted to determine the optimal dosing strategy for continuous intravenous infusion fentanyl in overweight/obese children.